2006
DOI: 10.2174/157015906778019482
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of TRP Channels in Mechanisms of Temperature and Pain Sensation

Abstract: Abstract:Pain is universal and vital to survival. It is an essential component of our sense of touch; together, touch and pain have evolved to enable our awareness of the intricacies of our environment and to warn us of danger and possible injury. There is a clear link between temperature sensation and pain-painful temperature sensations occur acutely and are a hallmark of inflammatory and chronic pain disorders of the nervous system. Mounting evidence suggests a subset of Transient Receptor Potential (TRP) io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 166 publications
(285 reference statements)
0
40
0
Order By: Relevance
“…The thermosensory system was evaluated psychophysically by Greenspan et al [20] and their findings indicated that 45 C is the average threshold for heat. Story [21] suggested that Transient Receptor Potential (TRP) ion channels activated by temperature are important molecular players in acute inflammatory and chronic Table 3 Operation sequence of the heater in three operational modes.…”
Section: Effect Of Pcm In Heat Sink Without Finmentioning
confidence: 99%
“…The thermosensory system was evaluated psychophysically by Greenspan et al [20] and their findings indicated that 45 C is the average threshold for heat. Story [21] suggested that Transient Receptor Potential (TRP) ion channels activated by temperature are important molecular players in acute inflammatory and chronic Table 3 Operation sequence of the heater in three operational modes.…”
Section: Effect Of Pcm In Heat Sink Without Finmentioning
confidence: 99%
“…Besides cold, it is also activated by various, mostly pungent and/or irritant compounds such as botanical substances like mustard oil, delta-9-tetrahydrocannabinol, eugenol, gingerol, methyl salicylate, allyl isothiocyanate, cinnamaldehyde, formalin, and nicotine [312][313][314][315]. Like TRPV1, TRPA1 is also considered as a key player of transduction of painful stimuli and a potential target of analgesic therapies [316][317][318][319].…”
Section: Trpa1mentioning
confidence: 99%
“…Because TRPM4 is Ca In addition to TRPC6 and TRPM4, the role of vanilloid family of TRP (TRPV) is also suggested in the mechanosensation of arteries (Liedtke et al, 2007). TRPV1-4 are originally known as heatsensitive NSC with differential ranges of threshold temperature for their activation (Story, 2006). Among the thermo-TRPV family, TRPV4 is also activated by osmotic stress (Phan et al, 2007), which might be associated with the mechanical stress during MR. Because MR requires physiological temperature, the putative role of TRPV in MR is worth of further investigation.…”
Section: Non-selective Cation Channel (Nsc)mentioning
confidence: 99%